The Use of Truth or Dare Games in Teaching Students' Speaking Ability at Senior High School - Afiqah Muflihah; Munir Munir; Muhammad Tahir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
Afiqah Muflihah, 2025. The Use of Truth or Dare Game in Teaching Students' Speaking Ability at Senior High School. A Thesis. English Department, Faculty of Languages and Literature. Universitas Negeri Makassar. (Supervised by Mr. Munir and Mr. Muh. Tahir). This study aims to determine the use of truth or dare game in teaching students' speaking ability at senior high school. The method used was quantitative with a pre-experimental research design with a sample 30 students of class XI MIPA 1. In obtaining data, the researcher used pretest and posttest as instruments. Result of the data analysis showed that by using Truth or Dare Game, students' speaking ability increased. This is evidenced by the t-test value wich is smaller than P (0.001 <0.05), which means that H0 in this study is rejected and H1 is accepted. So, it concluded that the use of Truth or Dare Game is effective in increasing the speaking ability of class XI MIPA 1 students at SMAN 1 Luwu.Keywords: Students' Speaking Ability, Truth or Dare Game